KECEMASAN MAHASISWA DALAM PRAKTIK PUBLIC SPEAKING (STUDI KASUS MAHASISWA MANAJEMEN PEMASARAN INDUSTRI ELEKTRONIKA ANGKATAN 2021) - Erlita Khrisinta Dewi (Nusantara Hasana Journal, 2022)
This study aims to find out the description of student anxiety in public speaking practice, the causes of students experiencing anxiety, and how to overcome anxiety in public speaking practice in the Electronics Industry Marketing Management Study Program, especially students in class of 2021. This research is a descriptive qualitative research. This qualitative research uses the case study method. Data was collected through observation, interviews and documentation. Data analysis techniques were carried out through three stages, namely, data reduction, data presentation, and drawing conclusions. The validity test used in this study uses trustworthiness, namely testing the truth and honesty of the subject in uncovering the reality according to what is experienced, felt or imagined. This study shows that the anxiety symptoms of 2021 MPIE Study Program students include physical, mental, and emotional symptoms. The causes of students experiencing anxiety in public speaking practice include lack of confidence, lack of preparation and practice, lack of experience, audience rejection, and unpleasant experiences in the past. The ways to overcome students' anxiety in public speaking practice can be done through self-adjustment, breathing exercises, changing body language, warming up, and anchoring.